ANALISIS UJI KIMIA KESADAHAN DAN BESI PADA AIR SUNGAI HULU BANGKO DENGAN MEDIA FILTRASI KARBON AKTIF KULIT KACANG TANAH - Ety Jumiati; Abdul Halim Daulay; Putri Indah Sari (Komunikasi Fisika Indonesia, 2022)
The filtering of river water has been carried out with the aim of knowing the edvantages of the river water upstream of Bangko before the filtration process is carried out, after the filtrations proces is caried out, and to determine the most optimum variation. In this study using the composition of activated carbon of peanut shells, silica sand, manganese, and zeolite with sample variations A (30% : 30% : 20% : 20%), B (35% : 25% : 20% : 20%), and C (40% : 20% : 20% : 20%). In this study, the chemical test parameters were: (hardness, and iron). The results of testing the river water before the filtration process has not met the PERMENKES RI No. 32 of 2017. Meanwhile, after the river water filtration process has met the clian waters standard based on the PERMENKES RI No. 32 of 2017. And the optimum variation is sample C with an activated carbon value of 40%.